2008
DOI: 10.1016/j.crohns.2008.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Is the efficacy of successful infliximab induction therapy maintained for one year lasting without retreatment in different behavior types of Crohn's disease?

Abstract: Infliximab induction therapy alone may result in sustained remission mainly in patients with luminal disease. These results suggest the need for maintenance therapy with infliximab after successful therapy induction in patients with fistulae, while luminal CD patients could possibly participate in regular retreatment only if needed. If these data are confirmed, this modification of the therapeutic procedure could well increase the cost-effectiveness of infliximab.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 8 publications
1
7
1
Order By: Relevance
“…First, clinical remission and relapse was based on phycisian's global assessment and not on the clinically validated scoring systems such as the Crohn's Disease Activity Index (CDAI). 7,9,10,13 This may have led to an underestimation of relapse rates observed in this study compared to other studies showing higher relapse rates 7-12 , although the complaints were never severe enough to justify reintroduction of medical or surgical therapy. Second, the study population was heterogeneous as the majority of the patients were treated episodically, which does not reflect the current clinical practice.…”
Section: Discussioncontrasting
confidence: 67%
See 2 more Smart Citations
“…First, clinical remission and relapse was based on phycisian's global assessment and not on the clinically validated scoring systems such as the Crohn's Disease Activity Index (CDAI). 7,9,10,13 This may have led to an underestimation of relapse rates observed in this study compared to other studies showing higher relapse rates 7-12 , although the complaints were never severe enough to justify reintroduction of medical or surgical therapy. Second, the study population was heterogeneous as the majority of the patients were treated episodically, which does not reflect the current clinical practice.…”
Section: Discussioncontrasting
confidence: 67%
“…[7][8][9][10][11][12][13][14] Based on this available information, it is now generally recommended not to stop anti-TNF therapy in IBD patients achieving clinical remission. 15,20,21 However, in a real-life clinical setting, it is highly unlikely that IFX can be continued throughout the life span of all IBD patients who have obtained clinical remission.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…43 Domenech et al found significantly increased relapse rates after stopping scheduled biologic therapy in patients with perianal disease compared with those with luminal disease only (82% vs 17%) after a mean follow-up period of 8.8 months. 40 This finding is also supported by a study by Molnar et al 44 Of the remaining studies, 2 were in a pediatric population. 45,46 Both examined the long-term effectiveness of anti-TNF and reported on outcomes after cessation in a small subset of patients.…”
Section: De-escalation Of Anti-tnf In CDsupporting
confidence: 76%
“…In most of the studies on withdrawal, patients had the anti-TNF discontinued while they were in clinical remission (with variable definitions of clinical remission and variable duration of remission before drug withdrawal). Relapse rates among those studies range from 21 to 56% at 12 months and from 47 to 64% at 24 month [104,105,106,107,108,109]. Further studies are still required in order to answer the question on whether maintaining the anti-TNF as opposed to reducing/discontinuing the drug is superior to maintain remission; as well as to define routine strategy in the future for long-term management of CD patients and to define the optimal withdrawal strategy [102,103].…”
Section: Withdrawal Of Anti-tnf Therapymentioning
confidence: 99%